1996
DOI: 10.1002/art.1780390802
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fas antigen‐mediated apoptosis of rheumatoid synovial cells in vitro by transforming growth factor β1

Abstract: Objective. To investigate the mitogenic and anti-apoptotic effects of transforming growth factor Pl (TGFPI) on rheumatoid synodal cells in vitro.Methods. Synovial cells were cultured with or wjthout TGFPl. After incdbatiod, the proliferative response of synoyial cells and the expression of Fas antigen and bcl-2 on synovial 'cells were examined. Finally, Fas hntigen-mediated apoptosis of synovial cells was investigated by the addition of anti-Fas antibody.Results. TGF/31 enhanced the proliferation of synovial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 43 publications
4
65
0
1
Order By: Relevance
“…However, little is known about the role of apoptosis in glandular destruction [9]. Recently, apoptotic cell death, especially Fasmediated apoptosis, has been reported to be involved in the development of other chronic inflammatory diseases such as RA [7] and UC [8]. Therefore, we examined both Fas/FasL and apoptotic cell death in the labial salivary glands from SS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the role of apoptosis in glandular destruction [9]. Recently, apoptotic cell death, especially Fasmediated apoptosis, has been reported to be involved in the development of other chronic inflammatory diseases such as RA [7] and UC [8]. Therefore, we examined both Fas/FasL and apoptotic cell death in the labial salivary glands from SS patients.…”
Section: Discussionmentioning
confidence: 99%
“…FasL protein was originally found in T cells [4], where diverse stimuli induced FasL gene expression [6,7], and it is believed that the expression of FasL is responsible for the killing activity of CD4 þ T cells and in part of CD8 þ T cells. The presence of apoptosis and the expression of Fas/FasL have been determined in the involved organs from human chronic inflammatory diseases such as the synovium from rheumatoid arthritis (RA) patients [7] and the colon from ulcerative colitis (UC) patients [8]. In addition, Kong et al have recently reported the expression of Fas/FasL in the salivary glands of patients with primary Sjögren's syndrome (pSS) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Following confirmation of the adequacy of permeabilization by trypan blue uptake, permeabilized cells were incubated with FITC-conjugated antiBcl-2 MoAb and examined by a flow cytometer. To check the adequacy of permeabilization on flow cytometric analysis, we used anti-a-tubulin MoAb (Cedarlane Labs, Ontario, Canada) as positive control antibody [7,18]. More than 99% of cells were positive with anti-a-tubulin MoAb.…”
Section: Flow Cytometric Analysis Of Fas and Bcl-2 On Thyrocytesmentioning
confidence: 99%
“…This peptide is a potent inducer of matrix protein synthesis. It is activated in a number of chronic inflammatory diseases, and it seems to mediate the perpetuation of synovial hyperplasia in RA patients (29). Diminution of TGFP expression could consequently be associated not only with matrix metabolism turnover, but also with the involution of pannus observed in chronic antigen-induced arthritis.…”
Section: Discussionmentioning
confidence: 99%